Superhero grief : the transformative power of loss - Harrington, Jill A.; Neimeyer, Robert A., 1954- (New York : Routledge, Taylor & Francis Group, 2021)
"Superhero Grief uses modern superhero narratives to teach the principles of grief theories and concepts and provide practical ideas for promoting healing. Chapters offer clinical strategies, approaches, and interventions, including strategies based in expressive arts and complementary therapies. Leading researchers, clinicians, and professionals address major topics in death, dying, and bereavement, using superhero narratives to explore loss in the context of bereavement and to promote a contextual view of issues and relationship types that can improve coping skills. This volume provides support and psychoeducation to students, clinicians, educators, researchers, and the bereaved while contributing significantly to the literature on the intersection of death, grief, and trauma"--
OCLC-licensed vendor bibliographic record.
Keywords: Grief; Loss (Psychology); Adjustment (Psychology); Superheroes -- Psychological aspects; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health